Legal Protection for Tolerance and Freedom Among Religious People in Indonesia - Mar'ie Muhammad Falah Akbar (Universitas Negeri Semarang, 2022)
Legal protection for tolerance and freedom among religious individuals in Indonesia is intricately linked to the country's foundational principles, particularly Pancasila, which emphasizes the divinity of the Almighty. Despite Indonesia's secular stance, it recognizes its religious identity, guaranteeing the rights of adherents of all faiths to practice their beliefs without discrimination or harm. This commitment to religious freedom is enshrined in the 1945 Constitution of the Republic of Indonesia, specifically in Articles 28E, 28J, and Article 29. These constitutional provisions serve as the cornerstone for safeguarding the rights of religious minorities and ensuring their legal protection within the Indonesian state. Moreover, legal protections extend to mitigate potential conflicts between religious freedom and the rights of others. According to the harm principle proposed by philosopher John Stuart Mill, limitations on religious freedoms are permissible when they impinge upon the rights and freedoms of others. This principle guides the Indonesian legal framework in balancing individual liberties with societal interests, promoting harmony and coexistence among diverse religious communities. Furthermore, the perspective advocated by human rights advocate Asma Jahangir underscores that restrictions on religious freedom primarily apply to the external forum, preserving individuals’ internal beliefs and practices. This nuanced understanding highlights the importance of respecting both individual autonomy and societal harmony within Indonesia's diverse religious landscape.